2015
DOI: 10.1016/j.eururo.2015.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 1577 Primary Prostate Cancers Reveals Novel Biological and Clinicopathologic Insights into Molecular Subtypes

Abstract: Background Prostate cancer (PCa) molecular subtypes have been defined by essentially mutually exclusive events, including ETS gene fusions (most commonly involving ERG) and SPINK1 over-expression. Clinical assessment may aid in disease stratification, complementing available prognostic tests. Objective To determine the analytical validity and clinicopatholgical associations of microarray-based molecular subtyping. Design, Setting and Participants We analyzed Affymetrix GeneChip expression profiles for 1,57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
112
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 47 publications
17
112
2
1
Order By: Relevance
“…DNA methylation cluster 1 contained twice the number of hypermethylated loci in comparison with cluster 3, and the epigenetic patterns were substantially different from those of ETV1 - and ETV4 -rearranged cancers, which exhibit more heterogeneous methylation levels. This diversity among ETS -positive subtypes is consistent with results from previous studies that suggest substantial molecular and clinicopathological differences between ERG - and non- ERG ETS -rearranged cancers [82, 83]. SPOP - and FOXA1 -mutant subsets showed homogeneous epigenetic profiles.…”
Section: Molecular Characteristics Of Prostatic Cancersupporting
confidence: 90%
“…DNA methylation cluster 1 contained twice the number of hypermethylated loci in comparison with cluster 3, and the epigenetic patterns were substantially different from those of ETV1 - and ETV4 -rearranged cancers, which exhibit more heterogeneous methylation levels. This diversity among ETS -positive subtypes is consistent with results from previous studies that suggest substantial molecular and clinicopathological differences between ERG - and non- ERG ETS -rearranged cancers [82, 83]. SPOP - and FOXA1 -mutant subsets showed homogeneous epigenetic profiles.…”
Section: Molecular Characteristics Of Prostatic Cancersupporting
confidence: 90%
“…These transcriptomic classifications were later confirmed, refined (Ando, Suguro, Kobayashi, Seto, & Honda, 2003;Guedj et al, 2012;Hu et al, 2006;Loi et al, 2007;Mackay et al, 2011;Rosenwald et al, 2002;Sørlie et al, 2001), used in preclinical models to stratify clinical trials (Barton, Hawkes, Wotherspoon, & Cunningham, 2012), and inspired the discovery of clinically and biologically heterogeneous subgroups in many other malignancies, including colorectal cancer (Budinska et al, 2013;De Sousa E Melo et al, 2013;Marisa et al, 2013;Roepman et al, 2014;Sadanandam et al, 2013;Schlicker et al, 2012), renal cell carcinoma (Brannon et al, 2012(Brannon et al, , 2010, glioma (Nutt et al, 2003;Shai et al, 2003), liver (Boyault et al, 2007;Chiang et al, 2008;Hoshida et al, 2009;Lee et al, 2004), bladder (Biton et al, 2014), prostate (Tomlins et al, 2015), acute myeloid leukemia (de Jonge, Huls, & de Bont, 2011;Mrózek, Radmacher, Bloomfield, & Marcucci, 2009;Silva et al, 2009;Verhaak et al, 2009), and other cancers (Barlin et al, 2015;de Reyni es et al, 2014;Guo et al, 2015).…”
Section: Transcriptomic Classificationsmentioning
confidence: 93%
“…In some studies [15,16], SPINK1 was considered as an activator of aggressiveness and was associated with poor biochemical failure in patients underwent radical prostatectomy. Whereas, results from recent studies with large-scale population showed that SPINK1 seemed to be not associated with adverse prognosis [17,18].…”
Section: Introductionmentioning
confidence: 91%